(untitled) (Context: Journal of Interdisciplinary Studies, 2022)
Context: Journal of Interdisciplinary Studies is a peer-reviewed scholarly journal committed to the advancement of interdisciplinary research in exploration of the most pressing and emerging key social and political issues of the 21st century. These include the implications of accelerated globalization, pluralism and diversity, human rights and freedoms, sustainable development, and inter-religious encounters. Researchers in the humanities and social sciences are invited to contribute to a better understanding of major moral and ethical issues through creative cross-pollination of ideas, perspectives, and methodologies. In an effort to bridge different cultures, the journal will also publish translations of significant articles. Context welcomes articles, essays and book reviews in all areas of interdisciplinary studies.